Incorporation of games mechanics as engagement tools for students in distance teaching system: a systematic review of the literature (Research, Society and Development, 2023)
The use of gamification as methodology for the engagement of students in non-games context has been widely used and researched in recent years. However, in order for a gamification project to be successfully implemented, it is necessary to understand, in the best possible way, the use of game mechanics in Learning Management System (LMS), of Distance Education courses. This article is the result of a Systematic Literature Review, from which 14 studies were analyzed presenting the correlation between the use of game mechanics and the engagement of elementary, secondary and higher education students. It is concluded that the use of games mechanic, by the use of gamification, has provided a greater involvement of students who use the gamified learning systems.